The City [within] The Drawing: The urban in the space of representation - Banou, Sophia (Interstices: Journal of Architecture and Related Arts, 2015)
This paper presents the installation The City [within] The Drawing, the conclusive piece in a series of four installations that engage in exploring the material and temporal limits of architectural drawing conventions. Consisting of both drawn and modelled elements, the installation brings together elements of the previous works in a cumulating transcription concerned with the negotiations that take place between the city and its representation, as well as between the drawing surface and the spatiality it inevitably suggests. The city serves both as the ground and the object of a representation, which proposes installation as a way to immerse in drawing as a spatial condition. The project places city and drawing within one another in an attempt to reveal the recursive semiotic interactions that emerge between space and representation through relations of situation and inhabitation.